The executive athlete : how sports psychology helps business people become world-class performers - Gerson, Richard F. (HRD Press, 2008)
"Executive athletes" practice and compete, win some and lose some. Then they do it all over again just like athletes. The Executive Athlete is all about the similarities between executives who want to achieve high levels of performance and athletes who play at the top of their game. Dr. Gerson has spent years coaching, testing and training business people to use sport psychology to better their performances. He's found you get measurable performance improvements if you treat and train business people like athletes. He takes you inside the minds of athletes and shows you how they mentally tra.